Upwardly mobile townies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Responding to the cover article 'Take Your Farm to the City' in Spore 81, Jean Revol of Montélimar, France, is concerned that urban agriculture means bad news for cities. 'Africa's cities are spreading wildly, with no planning and vegetation, and...